2013
DOI: 10.1089/end.2012.0725
|View full text |Cite
|
Sign up to set email alerts
|

Modified Complete Supine Percutaneous Nephrolithotomy: Solving Some Problems

Abstract: Modified csPCNL is a safe and effective procedure with excellent outcomes and a low rate of major complications. It provides a good area for renal puncture and surgical instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…BMI, body mass index; ESWL, extracorporeal shockwave lithotripsy. [27]; (2) the percutaneous nephroscopy channel in the oblique-supine position is mostly around 0°, leading to low intrapelvic pressure, thereby declining the possibility of reflux sepsis from urine [28] and helping flushing out fragmented stones; (3) it can be combined with the modified lithotomy position, which enables completion of body positioning, sterilization and draping in one time, and on both regions of the pudendum and waist, avoiding position change, hence saving operative time and improving efficiency; and (4) if necessary, specific cases could be operated with superior and inferior double endoscopy, or puncture condition and guide wire placement could be identified under direct vision of the ureter and renal pelvis, increasing operation safety. In order to achieve the inclined angle of the obliquesupine position, authors suggested pulling or padding methods to expose the waist and hypochondrial region [22,23,29].…”
Section: Discussionmentioning
confidence: 99%
“…BMI, body mass index; ESWL, extracorporeal shockwave lithotripsy. [27]; (2) the percutaneous nephroscopy channel in the oblique-supine position is mostly around 0°, leading to low intrapelvic pressure, thereby declining the possibility of reflux sepsis from urine [28] and helping flushing out fragmented stones; (3) it can be combined with the modified lithotomy position, which enables completion of body positioning, sterilization and draping in one time, and on both regions of the pudendum and waist, avoiding position change, hence saving operative time and improving efficiency; and (4) if necessary, specific cases could be operated with superior and inferior double endoscopy, or puncture condition and guide wire placement could be identified under direct vision of the ureter and renal pelvis, increasing operation safety. In order to achieve the inclined angle of the obliquesupine position, authors suggested pulling or padding methods to expose the waist and hypochondrial region [22,23,29].…”
Section: Discussionmentioning
confidence: 99%
“…. For supine positioning, we used the modified complete supine position that has been previously described .…”
Section: Methodsmentioning
confidence: 99%
“…Vicentini et al [13] described a modified technique placing the patients in a supine decubitus position with the posterior axillary line located just outside the border of the surgical table and the flank extended. Aimed at increasing the space between the last rib and the iliac crest.…”
Section: General Aspects Of Supine Positionmentioning
confidence: 99%